Photonic crystal fibre devices for sensing applications - Shen, Zhanyu. (2013)
In this Final Year Project, the thermo-properties of PCF was changed by using non-selective infiltration methods, and modal interferometers were fabricated using fully ethanol-filled hollow core PCF for temperature sensing purpose. Also, the temperature sensitivity of the PCF based model interferometer was adjusted using selective infiltration technique.